KINERJA DAY SPA DI KECAMATAN KUTA SELATAN, BALI - I Gede Darmawijaya (Jurnal Ilmiah Hospitality Management, 2011)
Spa industry is a fast growing industry in the world. In Indonesia, this industry grew 174% since 2003. This fenomena also happened in Bali especially in South Kuta Distric Badung Regency.  The annual average growth of numbers of day spas in this area is 40% since 1995. In order that spa businesses can see their performance, they need to benchmark with day spa industry’s performance. Based on these reasons this research was composed in the aim of revealing the performance of day spa in South Kuta Distric. This research made use 50 day spas to get the data. These 50 day spas are the day spas population in South Kuta Distric.  The instrument used is questionnair focusing on spa key performance indicators. The findings of this research are (1) average spa occupancy rate is 19%; (2) average treatment price/hour IDR 67.872; (3) RevPATH day spa is IDR 12.895; (4) average spa revenue per m2 per year is IDR 510.985; (5) average revenue per employee per year is IDR 51.919.318; (6) average number of guest per spa per year are 5887 persons or 16 persons per day ; (7) average number of guests per employee per year are 591 persons; and (8) average number of treatment hours sold per employee per year  are 765 hours